(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
Hazardous organic pollutants are a common environmental problem, as they do not readily decompose in the environment, leading to their accumulation and a negative impact on ecosystems and human health. Therefore, finding effective and sustainable ways to dispose of them is crucial for preserving the environment and mitigating the health risks associated with them. Consequently, this work demonstrated a cost-effective, environmentally friendly, and straightforward technique for creating a zinc oxide nanocomposite using potato peels (PP).This nanocomposite, known as ZnO-PP,was synthesized and then combined with metakaolin yo from a composite with the prepared material to form a composite designed to facilitate an advanced oxidation process (AOP) for the removal of basic fuchsin (BF) from aqueous media.Comprehensive characterization of the synthesized composites was performed using several analytical instruments, including Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Field-Emission Scanning Electron Microscopy (FESEM),and Brunauer–Emmett–Teller (BET) surface area analysis. The BET results indicated specific surface areas of 2.95 m²/g for raw potato peels (PP), 15.985 m²/g for ZnO-PP, 28.251 m²/g for ZnO-MK composite. Under optimal conditions, namely a ZnO-MK dosage of 0.15 g per 100 mL solution, an initial BF concentration of 10 mg/L, a contact time of 120 minutes, and pH 7 the composite achieved a maximum dye removal efficiency of 96%. Kinetic evaluation revealed that the degradation of BF conformed to a pseudo-first-order rate model, with a coefficient of determination (R²) of 0.9526. Hazardous organic pollutants are a common environmental problem, as they do not readily decompose in the environment, leading to their accumulation and a negative impact on ecosystems and human health. Therefore, finding effective and sustainable ways to dispose of them is crucial for preserving the environment and mitigating the health risks associated with them. Consequently, this work demonstrated a cost-effective, environmentally friendly, and straightforward technique for creating a zinc oxide nanocomposite using potato peels (PP).This nanocomposite, known as ZnO-PP,was synthesized and then combined with metakaolin yo from a composite with the prepared material to form a composite designed to facilitate an advanced oxidation process (AOP) for the removal of basic fuchsin (BF) from aqueous media.Comprehensive characterization of the synthesized composites was performed using several analytical instruments, including Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Field-Emission Scanning Electron Microscopy (FESEM),and Brunauer–Emmett–Teller (BET) surface area analysis. The BET results indicated specific surface areas of 2.95 m²/g for raw potato peels (PP), 15.985 m²/g for ZnO-PP, 28.251 m²/g for ZnO-MK composite. Under optimal conditions, namely a ZnO-MK dosage of 0.15 g per 100 mL solution, an initial BF concentration of 10 mg/L, a contact time of 120 minutes, and pH 7 the composite achieved a maximum dye removal efficiency of 96%. Kinetic evaluation revealed that the degradation of BF conformed to a pseudo-first-order rate model, with a coefficient of determination (R²) of 0.9526.